Analisis Kesiapan Lembaga Profesi Akuntansi Di Era Industri 4.0 - Bagus Andi Kriswoyo; zul azmi; Siti Samsiah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2020)
The purpose of this research is to find out what factors affect the readiness of the accounting professional institutions, in this case the Indonesian Accounting Association (IAI) and how these factors affect the readiness of IAI as an accounting professional institution in facing and providing added value to accountants in the industrial era. 4.0. The factors identified and used in this research are mental revolution, education and training system, change in work culture, and basic principles of accounting profession ethics. The data was obtained through in-depth interviews with informants who were the administrators of IAI Riau Region. The analytical tool used in this study is the NVivo 12. The research results show that the mental revolution, education and training systems, changes in work culture, and basic principles of professional accounting ethics have prepared in the face of and can provide added value to accountants in the industrial era 4.0.